Penerapan Model Pembelajaran Kooperatif Tipe Think Talk Write (TTW) pada Pokok Bahasan Ekosistem untuk Meningkatkan Hasil Belajar Siswa Kelas VII A SMP Nurul Anwar Desa Pakel Kecamatan Montong Kabupaten Tuban Tahun Pelajaran 2016/2017 - Sholikah, Uswatun; Mawartiningsih, Lilik (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
This research is based on the result of early observation of biology learning in class VII A SMP Nurull Anwar Desa Pakel Subdistrict Montong Tuban District showing some obstacles in the implementation of KBM, ie learning is still dominated by teachers so that students are less active in learning. The average value obtained by students 62.90. This is not in accordance with the KKM that reaches 75. This study aims to improve biology learning outcomes to be better, both individual values and classical values. To achieve that goal, the researcher uses the TTW (think talk write) model, which is in this learning. Students are asked to make notes from the reading result individually (think). Students then interact and collaborate with friends to discuss the discussed tasks previously shared Teacher (talk). Furthermore, the students write the result of the discussion (write). The research method used is Classroom Action Research Method (PTK), Action Research This class is carried out in 2 cycles. The subjects of the study were the students of class VII A Junior High School Nurul Anwar Pakel Village, Montong District, Tuban Regency in the academic year 2016/2017, which numbered 28 students. The instrument used in this study is the test of learning and observation. Learning result test is used to measure student's success, observation is used through observation format to measure teacher and student performance in learning. The results showed an increase in value between before the study, cycle I and cycle II. Previously, before the research the average value of students is only 62.90, then the value of the cycle I score in the average student obtained 72.25 with 72% complete learning. The second cycle average value increased to 87.49 with 87.50% complete learning. Thus it can be concluded that student learning outcomes both individually and classically can be improved through the TTW learning model, it is suggested that biology learning with this approach can be used as an alternative method of teacher in delivering the subject matter especially on biology.